Prognostic significance of antifibrotic agents in idiopathic pulmonary fibrosis after initiation of long-term oxygen therapy - Ishiwari, Mayuko; Kono, Yuta; Togashi, Yuki; Kobayashi, Kenichi; Kikuchi, Ryota; Kogami, Mariko; Abe, Shinji (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Idiopathic pulmonary fibrosis (IPF) is a fatal and progressive interstitial lung disease with varying degrees of hypoxemia. Long-term oxygen therapy (LTOT) is frequently used to treat hypoxemia, however the prognostic factors for better survival in IPF patients after initiation of LTOT remain unknown. Methods: We retrospectively investigated favorable factors of survival in consecutive 55 IPF patients with chronic respiratory failure who were introduced LTOT. Results: The 6-, 12-, 18-, and 24-month survival rates in IPF patients after introduction of LTOT were 70.9%, 49.0%, 45.2%, and 32.3%, respectively. Univariate analysis demonstrated that low Glasgow Prognostic Score (GPS) (hazard ratio [HR] 0.482, p=0.043) and treatment with antifibrotic agents (HR 0.401, p=0.013) were associated with favorable survival, while multivariate analysis revealed that treatment with antifibrotic agents was the independent predictor (HR 0.449, p=0.032). Moreover, IPF patients treated with antifibrotic agents with LTOT had significantly longer survival than those without antifibrotic agents (p = 0.0106). Conclusion: In IPF patients who were introduced LTOT, treatment with antifibrotic agents was the independent factor for favorable survival. Treatment with antifibrotic agents may improve prognosis of IPF even after initiation of LTOT.